2022
DOI: 10.3389/fgene.2022.788670
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pyroptosis-Related Subtypes via RNA-Seq and ScRNA-Seq to Predict Chemo-Immunotherapy Response in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is associated with poor prognosis and invalid therapeutical response to immunotherapy due to biological heterogeneity. There is an urgent need to screen for reliable indices, especially immunotherapy-associated biomarkers that can predict patient outcomes. Pyroptosis, as an inflammation-induced type of programmed cell death, is shown to create a tumor-suppressive environment and improve the chemotherapeutic response in multiple tumors. However, the specific therapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…We found that relevant genes from PMSN‐mediated SDT were mainly involved in interleukin‐1 production, positive regulation of superoxide anion generation, positive regulation of inflammasome complex regulation of inflammatory response, pyroptosis, cysteine‐type endopeptidase activity involved in apoptotic process, cysteine‐type endopeptidase activator activity, and cytokine receptor binding in GO analysis (Figure S19b, Supporting Information). Additionally, among the genes, we selected 23 pyroptosis‐ ( Casp3, Casp4, Casp1, Casp9, Casp8, Gsdme, Gsdmd, Gsdmc, Gsdma, Nlrc4, Nlrp3, Pycard, Naip2, Aim2 Pjvk , and Nlrp1 ) and pro‐inflammatory cytokine‐ ( Il18, Il1b, Tnf, Il6, Ila, Csf2 , and Csf1 ) related genes [ 38 ] from identified differentially expressed genes (DEGs). After PMSN+US treatment, Casp3, Gsdme, Naip2 , and Il18 had significant upregulation ( p < 0.005), Casp4, Casp1, Casp9, Casp8, Gsdmd, Nlrc4, Nlrp3, Il1b , and Tnf were also enriched in tumors ( p < 0.05), while Pjvk and Nlrp1 were downregulated ( p < 0.05) when comparing to the NTC group (Figure 3i).…”
Section: Resultsmentioning
confidence: 99%
“…We found that relevant genes from PMSN‐mediated SDT were mainly involved in interleukin‐1 production, positive regulation of superoxide anion generation, positive regulation of inflammasome complex regulation of inflammatory response, pyroptosis, cysteine‐type endopeptidase activity involved in apoptotic process, cysteine‐type endopeptidase activator activity, and cytokine receptor binding in GO analysis (Figure S19b, Supporting Information). Additionally, among the genes, we selected 23 pyroptosis‐ ( Casp3, Casp4, Casp1, Casp9, Casp8, Gsdme, Gsdmd, Gsdmc, Gsdma, Nlrc4, Nlrp3, Pycard, Naip2, Aim2 Pjvk , and Nlrp1 ) and pro‐inflammatory cytokine‐ ( Il18, Il1b, Tnf, Il6, Ila, Csf2 , and Csf1 ) related genes [ 38 ] from identified differentially expressed genes (DEGs). After PMSN+US treatment, Casp3, Gsdme, Naip2 , and Il18 had significant upregulation ( p < 0.005), Casp4, Casp1, Casp9, Casp8, Gsdmd, Nlrc4, Nlrp3, Il1b , and Tnf were also enriched in tumors ( p < 0.05), while Pjvk and Nlrp1 were downregulated ( p < 0.05) when comparing to the NTC group (Figure 3i).…”
Section: Resultsmentioning
confidence: 99%